Hard X-Rays from NGC 4151: A Thermal Origin? - Titarchuk, Lev; Mastichiadis, Apostolos (1994)
We present a model for explaining the recent combined X-ray and low- energy gamma-ray observations of the Seyfert galaxy NGC 4151. According to this model, soft photons become Comptonized in a hot spot producing simultaneously the low-energy power law as observed by Ginga and the high-energy cutoff observed by OSSE. Implementing recently developed theoretical calculations toward a generalized theory of Comptonization, we were able to find fits to the observations using only two parameters which characterize the physical quantities of the emission region: the plasma cloud optical depth and its temperature. We find that there is no need for additional nonthermal, reflection, or higher temperature thermal components to fit the aforementioned OSSE and Ginga observations. We derive in addition the size of the photon region and the temperature of the upscattered soft photons. We should emphasize, also, that any attempt at fitting only the high-energy parts of the spectrum (photon energies > 60 keV) by the Sunyaev & Titarchuk (1980) nonrelativistic Comptonization model leads to an underestimate of the Comptonization parameter γ (or, equivalently, to an overestimation of the X-ray power-law spectral slope) and leads, as a result, to incorrect proportions between the low-energy and high-energy parts of the spectrum.
Keywords: Astronomical Models; Astronomical Spectroscopy; Astrophysics; Compton Effect; galaxies: Seyfert; Gamma Ray Astronomy; Gamma Ray Spectra; Ginga Satellite; Mathematical models; Optical Thickness; Plasma Temperature; PLASMAS; Power Series; radiation mechanisms: thermal; Radiative Heat Transfer; radiative transfer; relativity; Scintillation Counters; Seyfert Galaxies; Space Plasmas; X Ray Astronomy; X Ray Spectra